Diagnostic Performance of CT Scan in Sinonasal Mass - Lodh, Dipankar; Nazmul, Islam; Debesh, Talukder; Rita, Majumder; Shahriar, Arafat; Zahirul, Islam (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: CT imaging of nose and paranasal sinuses is to confirm the diagnosis, localize the disease, characterize the extent of pathology and describe any anatomical variations. A careful histopathological examination (HPE) is nesessary to decide the nature of a specific lesion. Objective: To observe performance of CT scan as a sensitive modality in the diagnosis of sinonasal mass by comparing with the findings of histopathological examination. Methods: This cross sectional study in Dhaka Medical College Hospital (DMCH). From 01/ 07/2013 to 30/06/2014 (One year), 42 patients were selected. Resuls: Here male and female ratio was found 1.4:1 So, the incidence of sinonasal growth slightly higher in male (59.3%) compared to the female (40.6%).Incidence of malignant tumour was found more in age group above 60 years. Out of 32 patients, 6 patients (18.7%) were diagnosed histopathologically as infective, 7 patients (21.8%) were benign and 19 patients (59%) had malignant sinonasal mass. Bangladesh J Otorhinolaryngol; October 2017; 23(2): 164-170